الإرسالية الاشهارية التلفزيونية المعولمة وأبعادها القيمية . - دراسة تحليلية لإشهار بانادول اكسترا- - ام الرتم, سحر (جامعة الوادي - University of Eloued, 2022)
تبحث هذه الدراسة موضوع الرسالة الاشهارية التلفزيونية في القنوات الفضائية العربية وتأثيرها على المنظومة القيمية للمجتمعات، من خلال التركيز على ابراز التمثلات القيمية والثقافية التي تحملها الصورة الاشهارية عبر الصور والأيقونات والعلامات ، حيث تفرض دراسة الاشهار التمييز بين قطبين أساسيين متباينين ومتكاملين في الآن نفسه، ويتمثلان في البعد السوسيو- اقتصادي الذي يوجد خارج الخطاب الاشهاري، ويتكفل بدفع المتلقي إلى القيام بفعل الشراء، والبعد الخطابي بصفته نسيجا تتشابك فيه مجموعة من العلامات وفق قواعد تركيبية ودلالية، فالاشهار يأخذ من التقدم الاقتصادي وعولمة الرأسمالية ذريعة ليقوم بتنميط ثقافي واحد في البلدان العربية فيقوم بتحطيم الشخصية الوطنية وتذويبها في بوتقة الاستهلاك للمنتوجات والتصرفات و السلوكيات، وتغرس عادات وأفكار الدول الغربية. This study examines the issue of the television advertising message on Arab satellite channels and its impact on the value system of societies ; By focusing on highlighting the value and cultural representations that the advertising image carries through images and icons ; Where the study of advertising imposes a distinction between two basic poles that are different and complementary at the same time, They are represented in the socio-economic dimension, which is outside the advertising discourse, and is responsible for pushing the recipient to make the act of purchasing, and the rhetorical dimension as a fabric in which a set of signs are intertwined according to synthetic and semantic rules. Publicity takes economic progress and the globalization of capitalism as a pretext for a single cultural stereotyping in the Arab countries, destroying the national character and dissolving it in the crucible of consumption of products and behaviors, and instilling the habits and ideas of Western countries.
The globalized television advertising mission and its value dimensions - Analytical study of the publicity of Panadol Extra –
مقال
Keywords: الاشهار، الصورة الاشهارية ، الاشهار التلفزيوني ، الاشهار المعولم ، القيم; Advertising, advertising image, television advertising, globalized advertising, values.